The Case of Leprosy in Work Area of Talango Health Center in Sumenep Regency: Case Control Study - Fetty Rhomdani; Lilis Sulistyorini (JURNAL KESEHATAN LINGKUNGAN, 2020)
Introduction: Leprosy was caused by Mycobacterium leprae infection which attacks the peripheral nerves and human skin. A total of 39 cases of leprosy occurred in 2018 at the Talango Health Center and became the highest prevalence in Sumenep Regency each year. Multibacillary leprosy dominates in 76.92% of cases. This study aims to analyze the influence of physical environment factors of the home namely temperature, humidity, ventilation, occupancy density, natural lighting, wall types, and floor types on the incidence of leprosy in Talango Health Center. Method: This type of research was observational analytic with a case-control research design. The respondent chosen was 25 cases and 25 controls, taken using simple random sampling. Data were collected through observation sheets which included measurements of temperature, humidity, ventilation, occupancy density, natural lighting observations, types of walls and floors. Data analysis using a chi-square test. Result and Discussion: The results of this study indicate that there was a significant correlation of ventilation variables (p = 0,03) and natural lighting (p = 0,04), whereas in the temperature (p = 1,00), humidity (p = 0,48), occupancy density (p = 1,00), wall type (p = 1,00), and floor type (p = 1,00) found no significant correlation. The physical environment of the house has not received special attention from the local community. As long as they were still comfortable living with these conditions there was no need to take any action. Conclusion: The community needs to be increased awareness by counseling and increasing knowledge of the dangers of the physical environment of the house that were not properly maintained at minimum health standards.